Investigating Doxorubicin’s mechanism of action in cervical cancer: a convergence of transcriptomic and metabolomic perspectives - Huang, Zhuo; Jing, Huining; Lv, Juanjuan; Chen, Yan; Huang, YuanQiong; Sun, Shuwen (Frontiers in Genetics, 2023)
Introduction: Cervical cancer remains a significant global health burden, and Doxorubicin is a crucial therapeutic agent against this disease. However, the precise molecular mechanisms responsible for its therapeutic effects are not fully understood. Methods: In this study, we employed a multi-omics approach that combined transcriptomic and metabolomic analyses with cellular and in vivo experiments. The goal was to comprehensively investigate the molecular landscape associated with Doxorubicin treatment in cervical cancer. Results: Our unbiased differential gene expression analysis revealed distinct alterations in gene expression patterns following Doxorubicin treatment. Notably, the ANKRD18B gene exhibited a prominent role in the response to Doxorubicin. Simultaneously, our metabolomic analysis demonstrated significant perturbations in metabolite profiles, with a particular focus on L-Ornithine. The correlation between ANKRD18B gene expression and L-Ornithine levels indicated a tightly controlled gene-metabolite network. These results were further confirmed through rigorous cellular and in vivo experiments, which showed reductions in subcutaneous tumor size and significant changes in ANKRD18B, L-Ornithine, and Doxorubicin concentration. Discussion: The findings of this study underscore the intricate interplay between transcriptomic and metabolomic changes in response to Doxorubicin treatment. These insights could have implications for the development of more effective therapeutic strategies for cervical cancer. The identification of ANKRD18B and L-Ornithine as key components in this process lays the groundwork for future research aiming to unravel the complex molecular networks that underlie Doxorubicin’s therapeutic mechanism. While this study provides a solid foundation, it also highlights the necessity for further investigation to fully grasp these interactions and their potential implications for cervical cancer treatment.